Monitoring and modeling of PCB dry deposition in urban area - Lee, Wen-Jhy; Su, Chun-Ching; Sheu, Hwey-Lin; Fan, Yi-Chin; Chao, How-Ran; Fang, Guor-Cheng (Journal of hazardous materials, 1996)
Dry deposition and air sampling were undertaken simultaneously in the ambient air of an urban site by using several dry deposition plates, two MOUDIs (micro-orifice uniform deposited impactors), one NRI (Noll rotary impactor) and several PS-1 (General Metal Work, PS-1) samplers from January to May 1994 in Tainan City, Taiwan. The dry deposition plate, which had a smooth surface, was always pointed into the wind. The PCB (polychlorinated biphenyl) congeners were analyzed primarily by using a gas chromatograph with a 63Ni electron capture detector (ECD). The measured dry deposition flux of total PCBs varied between 3.48 and 6.79 μg m −2 per day and averaged ≈ 4.73 μg m −2 per day. This was up to three orders of magnitude higher than the fluxes measured at the Great Lake and remote areas and close to those measured at urban areas by previous studies. The particle-bound PCB homologue composition collected by the dry deposition plate varied between 0.76 μg g −1 (di-CBs) and 11.5 μg g −1 (hexa-CBs). This profile of PCB homologues is similar to the pattern of Aroclor 1260 which is dominant in hexa-CBs and hepta-CBs. Because of their higher vapor pressure, in general, the less-chlorinated PCB homologues have a greater PCB mass fraction in the gas phase. The mean dry deposition velocities of PCB homologues ranged between 0.09 and 0.58 cm s −1. In general, the more highly chlorinated PCB homologues have a higher dry deposition velocity. Particle size distributions ( dC d(log D p ) vs. D p) of total PCBs were found to be bimodal. The highest peak was localized in the particle size range between 5.6 and 10.0 μm and the second peak was localized in the particle size range between 0.31 and 0.52 μm. The particle MMD 0 of total PCBs was 1.68 μm and more than 85% of the PCB mass was found in the particles smaller than 10 μm. By using the particle size distribution data, the dry deposition model used in this study can provide a good prediction for the dry deposition flux of total particle mass, total PCBs and PCB homologues. For both total particle mass and total PCBs, more than 87.5% of the dry deposition flux is contributed by particles of size > 10 μm. This is because particles larger than 10 μm have a higher dry deposition velocity (> 2.60 cm s −1) and, therefore, control the majority of the dry deposition flux.